Interval Valued D-Implications - Reiser, R.H.S.; Bedregal, B.C.; Santiago, R.H.N; Dimuro, G.P. (Trends in Computational and Applied Mathematics, 2009)
The aim of this work is to introduce the concepts of interval Dimplicationsand automorphisms, analyzing their main properties and establishingthe relation between them. Also, interval D-implications are related with punctualD-implications and automorphisms.